Optimalisasi Jembatan Lama Kediri sebagai Wisata Edukatif melalui Perspektif Ilmu Pengetahuan Sosial - Arifia Ayu Pradina Suci; Ulfi Aminatuz Zahroh (Program Studi Destinasi Pariwisata ISI Surakarta, 2026)
The Old Kediri Bridge is a historic colonial infrastructure that has undergone a shift in function from a main transportation route to an urban public space. This change in function opens up opportunities for utilizing the bridge as a cultural heritage-based educational tourism destination, but also presents challenges in maintaining a balance between recreational functions and heritage educational values. This study aims to analyze the optimization of the Old Kediri Bridge as an educational tourism destination from a Social Sciences perspective. The study employed a qualitative, descriptive-analytical design with data collection techniques including observation, interviews, questionnaires, and documentation studies. The results indicate that the Old Bridge holds strong historical, symbolic, social, and economic value, yet its use is still dominated by recreational purposes. This study concludes that optimizing educational tourism requires strengthening its interpretive function and sustainable management.